The Impact Of Gadget Use On Eye Health Disorders In Elementary School Students - Indirwan Hasanuddin; Zainab; Dewi Aulia Harianto; Sulkifli Nurdin; Arsad (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2022)
One of the communication tools that are often used today is a gadget. Gadget communication tools are one of the results of technological advances at this time. Over time many children and teenagers have used gadgets as both entertainment and learning media. As we know that the gadget screen itself uses small writing compared to books. So this results in a closer reading distance and will certainly increase the need for vision in its use which can cause visual symptoms such as eye fatigue blurred vision dizziness and dry eyes.This research is a type of quantitative research using analytic method with a retrospective design with a sample of 30 people with a total sampling technique. This research was conducted by carrying out eye examinations and filling out questionnaires by respondents to determine the impact of using gadgets on eye health problems in students at SDN 20 Pangsid Sidenreng Rappang Regency. The data obtained were then analyzed by univariate and bivariate using chi-square test. The results of this study are the results of measuring the intensity of gadget use and the status of eye health problems in students after filling out the questionnaire and eye examination using the Snellen chart the p-value 0.000 with a significance level of p < a (0,05) which means There is an Impact of Use Gadgets Against Eye Health Disorders in Students of SDN 20 Pangsid Sidenreng Rappang Regency.